The Importance Of Learning Curriculum Management For Institutional Quality - Nadliroh Nadliroh; Ria Yulia Gloria; Iis Arifudin; Sopidi Sopidi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study investigates the impact of curriculum management based on the POIE framework—Planning, Organizing, Implementing, and Evaluation—in improving institutional quality at MI Islamiyah Dinoyo Lamongan, a rural madrasah with various student backgrounds. Using quantitative approach was used to collect data from 38 respondents, including the principal, administrative personnel, and teachers. The measurement model results demonstrate that three dimensions of curriculum management (Planning, Organizing, Implementing, and Evaluation) meet validity standards; however, the Implementation indicator does not achieve the needed threshold, indicating inconsistencies between planned curriculum and instructional delivery. Institutional quality indicators (Leadership and Governance, Teacher Performance, Learning Outcomes, and Institutional Accreditation) have high validity, indicating their importance in measuring educational quality. Reliability tests show acceptable internal consistency for both constructs, with high Composite Reliability and AVE values indicating convergent validity. The findings show that curriculum management has a considerable impact on institutional quality, particularly in planning, organizational structure, and evaluation processes. However, the lack of execution highlights the need for greater pedagogical support. The study concludes that improving curricular implementation methods may boost overall institutional performance. This study helps to understand curriculum management in rural Islamic schools and has practical implications for increasing educational quality in similar circumstances